The Socio-Economic and Cultural Condition of Fisherman in Coastal Area of Sialang Buah, Teluk Mengkudu, Deli Serdang Regency, North Sumatera - Adria Wirda, Mona; Berutu, Nurmala; Rahmad, Riki (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This research aims to identify of coastal communities chartered economic potency, explore the human resources potency of coastal communities, investigate the role of coastal communities chartered economic institution, and knowing both of the socio-economic condition and infrastructure support for the economic development of coastal areas in Serdang Bedagai Regency. This research was done in Pantai Sialang Buah Desa Teluk Mengkudu, Serdang Bedagai Regency. respondents took by random sampling method. Data analysis method of this research was applied descriptive analysis. The result of this research shows that communities economics potency at coastal area quite prospective. The social economic condition of communities at coastal area relatively still very lag, although the economic sector is very potential to be developed like fishery sector, cultivation of seagrass, beach tourism, field crop and breeding sector. The role of the government and the private sector in developing the potential of coastal communities is not sufficient, especially in the field of infrastructure.